2018
DOI: 10.1016/j.bbmt.2017.10.010
|View full text |Cite
|
Sign up to set email alerts
|

A European HLA Isolate and Its Implications for Hematopoietic Stem Cell Transplant Donor Procurement

Abstract: Europeans have often been considered a homogenous group in registry donor match predictions, but it is now evident that HLA haplotype frequencies vary across the European continent. Earlier studies have indicated that Finns in northeastern Europe have unique HLA characteristics, and the increasing availability of high-resolution registry donor data is now making more detailed comparisons possible. In the first phase of the present study, estimated HLA haplotype frequencies in stem cell donor registries of Finl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 29 publications
2
32
0
Order By: Relevance
“…Poor (GF ≤ 5. 22 However, with few exceptions 9,23,24 no detailed analysis has been performed on the selected donors with respect to HLA and non-HLA characteristics.…”
Section: Mean Duration Registration (Y) Range (Y) Below 3 Y (%)mentioning
confidence: 99%
“…Poor (GF ≤ 5. 22 However, with few exceptions 9,23,24 no detailed analysis has been performed on the selected donors with respect to HLA and non-HLA characteristics.…”
Section: Mean Duration Registration (Y) Range (Y) Below 3 Y (%)mentioning
confidence: 99%
“…In the Finnish population, the common European HLA alleles and haplotypes as well as unique enrichments of haplotypes are presented. 42,43 .This was evident in a study where HLA-DRB1 imputation showed very low accuracy rate (<30%) for some alleles such as HLA-DRB1*01:01, HLA-DRB1*13:01, and HLA-DRB1*15:01 belonging to the five most frequent HLA-DRB1 alleles in the Finnish population when the reference material was from a large heterogeneous European population and not from the Finnish population. 44 Low imputation accuracy for HLA-DRB1 has also been described by other studies covering heterogeneous study cohorts or diverse ancestry groups.…”
Section: Current Methods For Hla Typingmentioning
confidence: 99%
“…Western and Eastern Finnish populations exhibit peculiar genetic features reflecting the settlement and population history of Finland. In the Finnish population, the common European HLA alleles and haplotypes as well as unique enrichments of haplotypes are presented …”
Section: Current Methods For Hla Typingmentioning
confidence: 99%
See 2 more Smart Citations